Green Finance in Europe – Strategy, Regulation and Instruments - Volker Brühl (Intereconomics, 2021)
A green transformation of nearly all parts of our economy is necessary, including but not limited to energy production and consumption, mobility, manufacturing and agriculture.
Keywords: 330